1991
DOI: 10.1161/01.cir.84.4.1481
|View full text |Cite
|
Sign up to set email alerts
|

A new method for quantitation of mitral regurgitation based on color flow Doppler imaging of flow convergence proximal to regurgitant orifice.

Abstract: Color flow Doppler provides new velocity information about the proximal FCR in patients with mitral regurgitation. According to the continuity principle, the maximal instantaneous regurgitant flow rate, obtained with the FCR method, may provide a quantitative estimate of the severity of mitral regurgitation, which is relatively independent of technical factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
2
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(85 citation statements)
references
References 21 publications
1
78
2
4
Order By: Relevance
“…The flow convergence or proximal isovelocity surface area (PISA) method is derived from the principle that as blood approaches a regurgitant orifice, its velocity increases, forming concentric shells of increasing velocity and decreasing surface area. 1,2 This surface area (PISA) can be estimated during 2-dimensional (2D) color Doppler (CD) echocardiography (2D-CD) assuming a hemispheric distribution of velocity vectors proximal to the regurgitant orifice. Under the principle of flow continuity, the severity of valve dysfunction can be quantified using PISA to determine the effective regurgitant orifice area and regurgitant volume.…”
mentioning
confidence: 99%
“…The flow convergence or proximal isovelocity surface area (PISA) method is derived from the principle that as blood approaches a regurgitant orifice, its velocity increases, forming concentric shells of increasing velocity and decreasing surface area. 1,2 This surface area (PISA) can be estimated during 2-dimensional (2D) color Doppler (CD) echocardiography (2D-CD) assuming a hemispheric distribution of velocity vectors proximal to the regurgitant orifice. Under the principle of flow continuity, the severity of valve dysfunction can be quantified using PISA to determine the effective regurgitant orifice area and regurgitant volume.…”
mentioning
confidence: 99%
“…10 The degree of MR was expressed qualitatively as 1+ to 4+ (3+ and 4+ was considered significant MR) and quantitatively as effective regurgitant orifice area (ERO), quantified as feasible, either with proximal isovelocity surface area method or with quantitative Doppler volumetric method. 11,12 Significant mitral regurgitation was defined as ERO > 0.2 cm 2 . In patients with trace mitral regurgitation ERO was considered null.…”
Section: Echocardiographic Evaluationmentioning
confidence: 99%
“…The proximal isovelocity surface area in the flow convergence region was imaged for the blood flow velocity of 29/ 27 cm/s during TTE/TEE by the corresponding first aliasing border, obtained by baseline shifting 4 (Fig. 2).…”
Section: Doppler Measurementsmentioning
confidence: 99%
“…Former studies using either TTE or TEE demonstrated comparable results. 4,7,9,10,16 Neither TTE nor TEE was able to differentiate between grades I and II or between grades III and IV mitral regurgitation because of a broad overlap of the measurements. This also agrees with data from the studies mentioned above.…”
Section: Comparison Between Echocardiography and Cardiac Catheterizationmentioning
confidence: 99%
See 1 more Smart Citation